Perinatal Outcomes Based on Number of Digital Exams in Patients with Preterm Prelabor Rupture of Membrane - Burd, Julia; Xie, Evaline; Kelly, Jeannie C.; Carter, Ebony B.; Odibo, Anthony; Zofkie, Amanda; Frolova, Antonina; Raghuraman, Nandini (American Journal of Perinatology, 2024)
The American College of Obstetricians and Gynecologists recommends speculum exams, rather than digital exams, for evaluation of the cervix after preterm prelabor rupture of membranes (PPROM). However, in clinical practice, digital exams may be necessary. We examined whether increasing numbers of digital exams were associated with adverse outcomes in PPROM.This was a single-center retrospective cohort study of patients admitted between 2019 and 2021 with PPROM at 24 to 34 weeks of gestation. The primary outcome was intra-amniotic infection and inflammation (triple I), compared between patients who had ≤1 or ≥2 digital exams during expectant management of PPROM. Secondary outcomes included latency, antepartum events, and other maternal and neonatal morbidities. Groups were compared using univariate analysis and Cox proportional hazards model to account for time between admission and delivery and potential confounders.Of 125 patients included in the analysis, 46 (36.8%) had ≤ 1 and 79 (63.2%) had ≥2 digital exams. There was no significant difference in triple I between groups (adjusted hazard ratio [aHR]: 1.03, 95% confidence interval [CI]: 0.47, 2.26). There were no significant differences in composite maternal or neonatal morbidities or latency from admission to delivery between groups (8 days [interquartile range (IQR): 3, 14] vs. 6 days [IQR: 3, 12]). There was a higher rate of spontaneous labor as the indication for delivery in the group with ≥2 exams (aHR: 2.07, 95% CI: 1.04, 4.11).In this retrospective cohort study, ≥2 digital exams during expectant management of PPROM was not associated with change in infectious morbidity or pregnancy latency. There was an increase in spontaneous labor in the group with more digital exams; this may be due to confounding by indication, as patients who are in prodromal labor are more likely to receive digital exams. These results suggest equipoise in exam type in the management of PPROM.
Keywords: speculum exam; pregnancy latency; PPROM; triple I; chorioamnionitis